Subclinical Renal Dysfunction in Horticultural Farmers: Early Detection in High Pesticide Exposure Areas - Hansen; Mursid Raharjo; Suhartono; Nur Endah Wahyuningsih (JURNAL KESEHATAN LINGKUNGAN, 2025)
Introduction: Globally, Chronic Kidney Disease of Unknown etiology (CKDu) poses a growing medical and social challenge, particularly in agrarian countries with a high prevalence of pesticide exposure. Indonesia, is one of the countries with a dominant agricultural sector. Tanjungsari and Glonggong villages in Wanasari subdistrict, Brebes Regency, are agricultural areas with a high intensity of pesticide use. Methods: This research aimed to identify the prevalence of subclinical renal dysfunction and associated risk factors in horticultural farmers in areas with high pesticide exposure. This research applied a cross-sectional method involving 40 farmers aged 26-65 years from two villages in Wanasari District, Brebes Regency. Data collection was carried out through interviews, and examination of kidney function biomarkers (serum creatinine and eGFR). Statistical analysis was conducted using Logistic Regression tests. Results and Discussion: The study revealed that 37.5% of participants exhibited eGFR values <90 ml/min/1.73 m2, indicating subclinical impairment of kidney function. Employment duration >20 years (p=0.024; OR=6.000; 95% CI:1.263-28.498) and daily working hours >6 hours (p<0.001; OR=69.279; 95% CI:6.423-756.965) showed a significant association with reduced eGFR values. Occupational health interventions should prioritize managing the duration and intensity of exposure to hazardous substances in the workplace, regardless of the workers' gender. Conclusion: The conclusion is that the daily working hours and the employment duration of the farmers are significantly associated with impaired kidney function, potentially acting as an initial marker of CKDu.